Inovasi dalam Implementasi Perencanaan Strategis untuk Pencapaian Visi Misi Uin Syarif Hidayatullah Jakarta - Fitriadi, Fitriadi; Zefrida, Yanuareza Hawa; Rachman, Farida Wijayanti (Kopertais Wilayah I DKI Jakarta dan Banten, 2025)
This study aims to provide an in-depth description of the innovations in the implementation of strategic planning to achieve the vision and mission of Syarif Hidayatullah State Islamic University Jakarta. The research employs a qualitative approach focused on gaining a deep understanding of the research problem. Through observations and interviews, the researcher identified the outputs of each stage in the form of documents, policies, or decisions related to steps taken to realize the institution’s vision and mission. Furthermore, the researcher conducted an analysis of these documents and activities to examine the interrelations among the processes, resulting in an integrated and comprehensive design.